ANALISIS PEKEMBANGAN PEMBANGUNAN JALAN USAHA TANI (JUT) TERHADAP PENDAPATAN SEKTOR PERTANIAN DI NAGARI TANJUNG BETUNG KABUPATEN PASAMAN - Siti Alina; Gina Havieza Elmizan (Jurnal Ekonomi dan Bisnis, 2025)
Farming Road (JUT) infrastructure development is infrastructure for agricultural development regarding food security, agricultural development, increasing income, agribusiness and farmer welfare. Intended as the main transportation route in agricultural areas which functions to facilitate mobility around agriculture, making it easier to transport production inputs and outputs. The implementation of JUT construction in Nagari Tanjung Betung has not been carried out evenly, there are several points that have been neglected and not completed on time, then the uneven development of JUT has caused income inequality among farmers. The aim of the research is to find out how development and farmers' income have progressed before and after the construction of JUT. This type of research is descriptive qualitative, Data collection methods through interviews, observation and documentation. The data analysis technique uses the Miles Huberman model which consists of data reduction, data presentation, and drawing conclusions. The results of the research show that the development of JUT in the last five years has seen an increase, decrease and stagnation in JUT development. JUT development will increase income in the agricultural sector. JUT development can increase agricultural productivity through land use and improve farmer performance such as maintaining, looking after and monitoring land more easily and quickly. Increased farmer productivity has a positive impact on farmer income. Each jorong in Nagari Tanjung Betung shows that JUT development resulted in production efficiency in the agricultural sector for farmers in Jorong Tanjung Betung before JUT 300% after JUT 365.8% difference in production efficiency 65.8%, farmers in Jorong Kauman Selatan before JUT 232.1% after JUT 273.3% difference in production efficiency 41.2%, and Jorong Kauman farmers before JUT 206.8% after JUT 250% the difference in production efficiency is 44.8% compared to before the JUT. The existence of JUT development increases production efficiency, the greater the efficiency ratio, the more efficient the production of rice and corn which has a positive impact on the income of the agricultural sector in Nagari Tanjung Betung.